2014
DOI: 10.1111/sdi.12338
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Use in End‐Stage Kidney Disease

Abstract: Clopidogrel irreversibly binds to the P2Y12 platelet receptor and acts as a potent inhibitor of platelet activation and aggregation. It is currently recommended for the prevention of cardiovascular events in patients with acute coronary syndromes, recent ischemic stroke, and peripheral arterial disease. Clopidogrel is a prodrug requiring hepatic conversion into its active metabolite. In the general population, genetic polymorphisms in the CYP2C19 gene interfering with hepatic conversion and the ABCB1 gene inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
(57 reference statements)
0
10
0
2
Order By: Relevance
“…25 CKD and end-stage kidney disease (ESKD) are independent risk factors for clopidogrel resistance; 50% to 80% of patients with ESKD have high on-treatment residual platelet reactivity (resistance) when treated with clopidogrel. 26 However, it has been suggested that the high burden of comorbidities in patients with CKD may account for this observation rather than CKD itself. 27 Overall, the current guideline recommendations to generally avoid primary prevention with aspirin in patients with CKD are reasonable in the context of recent randomized trials (ASPirin in Reducing Events in the Elderly study, Aspirin to Reduce Risk of Initial Vascular Events study, and A Study of Cardiovascular Events iN Diabetes) 28-30 that did not find aspirin to be beneficial for stroke prevention in other atrisk groups (elderly, moderate cardiovascular risk, and diabetes, respectively) ( Table 1).…”
Section: Primary Prevention Of Stroke In Ckd Antiplateletsmentioning
confidence: 99%
“…25 CKD and end-stage kidney disease (ESKD) are independent risk factors for clopidogrel resistance; 50% to 80% of patients with ESKD have high on-treatment residual platelet reactivity (resistance) when treated with clopidogrel. 26 However, it has been suggested that the high burden of comorbidities in patients with CKD may account for this observation rather than CKD itself. 27 Overall, the current guideline recommendations to generally avoid primary prevention with aspirin in patients with CKD are reasonable in the context of recent randomized trials (ASPirin in Reducing Events in the Elderly study, Aspirin to Reduce Risk of Initial Vascular Events study, and A Study of Cardiovascular Events iN Diabetes) 28-30 that did not find aspirin to be beneficial for stroke prevention in other atrisk groups (elderly, moderate cardiovascular risk, and diabetes, respectively) ( Table 1).…”
Section: Primary Prevention Of Stroke In Ckd Antiplateletsmentioning
confidence: 99%
“…Use of these precipitants may portend worsening renal function and/or dialysis. Advanced CKD and end‐stage kidney disease increase one's risk of bleeding due to platelet dysfunction and heightened risk of angioectasias (i.e., thin‐walled, dilated, ectatic blood vessels), which may be exacerbated in the setting of clopidogrel treatment . Cinacalcet, lanthanum, paricalcitol, and sevelamer are used almost exclusively in the treatment of abhorrent bone and mineral metabolism in persons with advanced CKD and end‐stage kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced CKD and end-stage kidney disease increase one's risk of bleeding due to platelet dysfunction 12 and heightened risk of angioectasias (i.e., thin-walled, dilated, ectatic blood vessels), 13 which may be exacerbated in the setting of clopidogrel treatment. 5,14,15 Cinacalcet, lanthanum, paricalcitol, and sevelamer are used almost exclusively in the treatment of abhorrent bone and mineral metabolism in persons with advanced CKD and end-stage kidney disease. These disorders of bone and mineral metabolism can lead to gastrointestinal mucosal calcinosis and calciphylaxis, 16 which may increase the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…51 52 Despite a hyperthrombotic phenotype, not all CKD patients respond effectively to clopidogrel, an inhibitor of platelet ADP receptor, and a commonly used antiplatelet medication. 49 50 53 54 This is important since poor response to clopidogrel has been associated with increased risk of death, MI, and stent thrombosis in patients undergoing PCI. 55 The antiplatelet effects of aspirin have also been reported to be reduced in patients with CKD, 56 although some studies reported no difference in platelet aggregation in CKD patients compared with non-CKD.…”
Section: From Chronic Kidney Disease and Fibrosis To Thrombosismentioning
confidence: 99%